1992
DOI: 10.1007/bf02253001
|View full text |Cite
|
Sign up to set email alerts
|

Extensive varices of ileocecum

Abstract: A man was admitted to our hospital because of intestinal reddish bleeding. Colonic varices were found at the cecum by colonoscopy. Angiography of the superior mesenteric artery showed that blood vessels were scant from the end of the ileum to the ascending colon. An operative view revealed the varices, but there was no trace of the ileocecal vein. This case, presenting a deficit of the ileocecal vein, indicated that the blood flow could not return via the ileocecal vein, and therefore there was an outflow thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Jejunal and ileal varices are rare but should be considered in such cases because bleeding from small bowel varices can be life threatening. Small bowel varices can occur in the absence of cirrhosis when there is mesenteric or splenic vein thrombosis, congestive heart failure, and congenital vascular abnormalities such as ileocecal vein deficit causing ileocecal varices [73]. Work-up should not be terminated simply because esophageal varices are found.…”
Section: Jejunal and Ileal Varicesmentioning
confidence: 99%
“…Jejunal and ileal varices are rare but should be considered in such cases because bleeding from small bowel varices can be life threatening. Small bowel varices can occur in the absence of cirrhosis when there is mesenteric or splenic vein thrombosis, congestive heart failure, and congenital vascular abnormalities such as ileocecal vein deficit causing ileocecal varices [73]. Work-up should not be terminated simply because esophageal varices are found.…”
Section: Jejunal and Ileal Varicesmentioning
confidence: 99%
“…In the patient who continues to have recurrent life-threatening bleeding, as ours did, the condition must be managed surgically. There are only eight cases in the literature of patients undergoing surgery for idiopathic colonic variceal bleeding (1,5,7,(9)(10)(11)(12)(13). The definite majority undergo segmental resections at an older age.…”
Section: Discussionmentioning
confidence: 95%
“…2 In a review of the literatures in PubMed from 1982 to 2007, a total of 14 cases was reported as ileal variceal bleeding. 1,4,5,7,[19][20][21][22][23][24][25][26][27][28] Among these 14 cases of ileal varix, 12…”
Section: Discussionmentioning
confidence: 99%
“…1,4,5,7,19,20,[22][23][24][25][26][27] All of theses cases, bar one had operations performed. 1,4,5,7,19,20,[22][23][24][25][26][27][28] 8 cases of them had a history of previous abdominal surgery. 1,4,19,22,23,[25][26][27] There were no cases that involved AVMs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation